Preferência alimentar e eficiência da carpa capim (Ctenopharyngodon idella) no controle de macrófitas aquáticas em mesocosmos - Silva, Adilson Ferreira da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The macrophytes may be problems in many water bodies, being necessary to employ control technique. The use of grass carp fish (Ctenopharyngodon idella) is an established biological control technique in many countries. The aim of this study was to evaluate the efficiency of food preference and control of diploid grass carp exposed the macrophytes Ceratophyllum demersum, Egeria densa, Egeria najas and Hydrilla verticillata isolated and combined condition micro and mesocosms. To this, three experiments were conducted. The first experiment was the supply and planting of macrophytes C. demersum, E. densa and E. najas in microcosms of 250 liters with five repetitions in completely randomized design (CRD). In the second and third experiment plants were offered in isolated and combinated condition mesocosms 2000 L. In the second experiment the plant C. demersum, E. densa and E. najas was used, in the third experiment the macrophyte C. demersum, E. densa, E, najas and H. verticillata in a randomized block design (RBD) in triplicate. In the first experiment the treatment with lower quantity of fish were what to show the bigger consumption and to get in weight in conditions of microcosms. In the second experiment the plant more predated by grass carp was E. najas and C. demersum when offered alone, and when offered together the order of food preference was C. demersum > E. najas > E. densa. In the third experiment the plant most consumed either alone or in combination was the H. verticillata and the least consumed was E. densa. Thus, it is concluded that use of grass carp (C. idella) as a biological control agent has advantages for having high rates of consumption and in greater preference for H. verticillata, followed by E. najas and C. demersum and lower intensity in the E. densa in mesocosms condition, which makes the grass carp one great tool for biological control

As plantas aquáticas podem constituir problemas em muitos corpos hídricos, sendo necessário empregar técnicas de controle. A utilização do peixe carpa capim (Ctenopharyngodon idella) é uma técnica consagrada de controle biológico em muitos países. Assim, o objetivo deste estudo foi avaliar a preferência alimentar e a eficiência de controle da carpa capim diploide, pelas macrófitas aquáticas submersas Ceratophyllum demersum, Egeria densa, Egeria najas e Hydrilla verticillata isoladas e combinadas em condição de mesocosmos. Para tanto, foram realizados 3 experimentos. No primeiro experimento foi realizado a oferta e o plantio das macrófitas C. demersum, E. densa e E. najas em microcosmos de 250 litros em delineamento inteiramente casualizado (DIC) com 5 repetições. No segundo e terceiro experimento as plantas foram ofertadas isoladas e associadas em condição de mesocosmos de 2000 L. No segundo experimento foi utilizada as plantas: C. demersum; E. densa e E. najas e no terceiro experimento: C. demersum; E. densa; E. najas e H. verticillata em delineamento em blocos casualizados (DBC) em triplicata. No primeiro experimento ocorreu maior controle e ganho em biomassa de peixe nos tratamentos com a menor quantidade de peixes. No segundo experimento a planta mais predada pela carpa capim foi a E. najas e C. demersum quando ofertadas isoladamente, e quando oferecidas em conjunto a ordem de preferência alimentar foi C. demersum > E. najas > E. densa. No terceiro experimento a planta mais consumida tanto isolada quanto combinada foi a H. verticillata e a menos consumida foi a E. densa. Assim, conclui-se que a carpa capim (C. idella) como agente de controle biológico apresentou elevada eficiência devido a sua maior preferência pela H. verticillata, seguida pela E. najas e C. demersum e com menor intensidade pela E. densa em condição de mesocosmos, o que torna a carpa capim uma ótima ...
Keywords: Carpa (Peixe); Peixe - Alimentação; Macrófitas aquáticas; Plantas aquaticas; Agentes no controle biologico de pragas; Aquatic macrophytes